Bodyworks - Graham, Nick; Walker, Richard
Each book in the Interactive Explorer series tackles a popular subject-the human body, oceans and rain forests, the animal kingdom, or weather and space-with a hands-on twist. With pulltabs that bring movement to the pages, flaps that reveal interesting facts, wheels that turn, die-cut windows that showcase incredible ideas, and acetate pages with dual layers, young readers will be fully engaged.From bones to blood, skin to saliva, kids can learn how every part of the body plays a role in keeping things running smoothly!